The Influence Of Online-Based Learning (E- Learning) On Students' Covert Behaviour In English Lessons AT SMAN 1 Barru - Taufik, Js; Anugrawati, Nunung; Ilmiah (Journal of Language Testing and Assessment, 2023)
This study aims to determine whether online based-learning (e-learning) affects students' covert behavior in English lessons at SMAN 1 Barru and explain the impact of online based-learning (e-learning) on students' covert behavior in English lessons at SMAN 1 Barru.  The population of this study was students of SMAN 1 BARRU.   This research is a descriptive study. The disguised behavior of social studies students of class XI SMA N 1 Barru falls into the category of less tingi with a percentage52,14% Judging from the results of the hypothesis test (t-test) obtained a calculation of 1.363 < ttabel 1.692 and a significant value of the implementation of e-Learning 0.182 > 0.05. The R value of 0.231 or 23.1% which means that the influence of the implementation of online-based learning (e-Learning) on student behavior covert is 23.1% while 76.9% is influenced by other variables that are not studied. With this, the implementation of online-based learning (e-learning) has no significant effect on the formation of covert behavior of students at SMAN 1 Barru.